2017
DOI: 10.1088/1361-6560/aa8a49
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of multimodality texture-based prediction models via optimization of PET and MR image acquisition protocols: a proof of concept

Abstract: Texture-based radiomic models constructed from medical images have the potential to support cancer treatment management via personalized assessment of tumour aggressiveness. While the identification of stable texture features under varying imaging settings is crucial for the translation of radiomics analysis into routine clinical practice, we hypothesize in this work that a complementary optimization of image acquisition parameters prior to texture feature extraction could enhance the predictive performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Radiomics analysis is easy to retrospectively perform on available imaging data; however, as there was heterogeneity in the MR acquisition parameters across multiple institutions, and even at a single institution, there might be changes in protocols over time. Variations in acquisition and image reconstruction parameters can introduce changes that are not due to underlying biologic effects, ie, the number of acquisitions, repetition time, echo time, and sampling bandwidth in T 2 imaging has been shown to affect texture analysis . To reduce bias and variance, we conducted this study prospectively and extracted all radiomics features from the same MRI unit using the same protocol at our institution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiomics analysis is easy to retrospectively perform on available imaging data; however, as there was heterogeneity in the MR acquisition parameters across multiple institutions, and even at a single institution, there might be changes in protocols over time. Variations in acquisition and image reconstruction parameters can introduce changes that are not due to underlying biologic effects, ie, the number of acquisitions, repetition time, echo time, and sampling bandwidth in T 2 imaging has been shown to affect texture analysis . To reduce bias and variance, we conducted this study prospectively and extracted all radiomics features from the same MRI unit using the same protocol at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in acquisition and image reconstruction parameters can introduce changes that are not due to underlying biologic effects, ie, the number of acquisitions, repetition time, echo time, and sampling bandwidth in T 2 imaging has been shown to affect texture analysis. 31,32 To reduce bias and variance, we conducted this study prospectively and extracted all radiomics features from the same MRI unit using the same protocol at our institution. Another especially critical and challenging component of radiomics is tumor segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…McGurk et al augmented PET images from 30 patients with soft tissue sarcoma by varying the extent of axial data combined per slice ("span"). 130 Simulated T1-weighted and T2-weighted MRI scans were acquired by varying the repetition time and echo time in a spin-echo pulse sequence, respectively. The impact of PET and MRI acquisition parameter variation on individual textures was investigated to assess the global response and the predictive properties of a texture-based model.…”
Section: Radiomics Phantomsmentioning
confidence: 99%
“…The results suggested that such a process is feasible for identifying an optimal set of image acquisition parameters to improve prediction performance. 130 Overall, these radiomics phantoms may be helpful in assessing the interscanner and intrascanner variabilities, and thus protocols for regular phantom quality assurance may be worth developing, similar to dosimetric study in current radiation therapy quality assurance programs, to monitor interscan and intervendor variability of imagederived features. In addition, phantom studies will also be useful in optimizing imaging protocols and image pre-/ postprocessing techniques that allow for reliable radiomics characterization.…”
Section: Radiomics Phantomsmentioning
confidence: 99%
“…In addition to the micro-heterogeneity associated with cell imaging and molecular markers of tumors based on medical imaging, there are recent categorizations and analyses of tumors and phenotypes, 12,13 localized regional modeling, 14 and applications such as prediction of future results. 15 Other, more quantitative, imaging models for specific tumor sites include head and neck, 16,17 lung, 18 breast, 19 liver, 20 cervix, 21 prostate, 22 limbs (sarcoma), 23 and the brain. 24 In the past five years, the field of radiology has garnered much more attention from experts in other fields, and the number of medical imaging publications has grown exponentially.…”
Section: Introductionmentioning
confidence: 99%